(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
Schematic illustration of a sustainable waste-to-resource approach for the synthesis of hybrid biodegradable hydrogels from PAN-based carpet manufacturing waste and cotton linter. Alkaline hydrolysis of PAN introduces hydrophilic carboxylate and amide groups, followed by crosslinking with different agents (citric acid, epichlorohydrin, MBAA, and glutaraldehyde) to form three-dimensional PAN–cellulose networks. The resulting hydrogels exhibit high water absorption, improved soil moisture retention, reduced irrigation demand, and tunable biodegradability, demonstrating their potential as eco-friendly soil amendments for sustainable agriculture in arid and semi-arid regions